Measuring the resistance of different substructure materials by sticking them to dentine with two different resin cements in vitro - Eratilla, V.; Yildiz, A. D.; Guven, S.; Eratilla, E. A.; Karaman, T.; Aguloglu, S.; Sumer, E. (Medknow Publications & Media Pvt Ltd, 2016)
Introduction: The resistance of three different substructure materials - metal (Cr-Co), zirconium (Zr), and ceramics (IPS Empress II) - was measured by sticking them to dentine with two different resin cements, a dual-cure resin cement (Panavia F 2.0 Light) and a self-adhesive resin cement (BisCem). Materials and Methods: In an in vitro study, 72 central upper front teeth were selected with no decay or apparent breakage and with complete development, removed for periodontal reasons. Labial and incisal surfaces of all teeth were prepared. Molds were obtained to prepare metal (Co-Cr), Zr, and ceramic (IPS Empress II) blocks for use in the study. The compressive strengths of the obtained material infrastructures were examined after thermal cycle processing by performing cementation to the teeth with two different cements. The data obtained were analyzed statistically. The Mann-Whitney U-test was used for comparisons of the groups with two options, and Kruskal-Wallis variance analysis was used to compare more than two groups. P < 0.05 were considered statistically significant. Results: While the highest result between samples was 117.86 +/- 47.94 N in the dual-cure (Panavia) -ceramic group, the lowest value was observed at 6.53 +/- 3.12 N in the self-adhesive (BisCem) -metal group. There was a significant difference between dual-cure (Panavia) and self-adhesive (BisCem) groups. Conclusion: In this study, we measured the bond strength; our most durable resistance groups were found to be, in order, Panavia-ceramics >Panavia-metal >Panavia-Zr >self-adhesive-ceramics >self-adhesive-Zr >and self-adhesive-metal.
Keywords: Adhesive system; bond strength; thermal cycle; zirconium